THE ORIGINS AND STAGES OF DEVELOPMENT OF THE OLD TATAR LITERARY LANGUAGE (Revista Inclusiones, 2019)
Among the Turkic languages, Tatar is an old written language and has a continuous writing and literary tradition, which goes back to the common Turkic literary tradition: the ancient Turkic, Karakhanid-Uygur. To achieve the goal, the following linguistic methods were used: descriptive, which has a number of linguistic observation techniques, as well as methods of classification and systematization; comparative historical, comparative research methods. A technique was developed which consists in evaluating synonymous and specific grammatical forms and phonetic phenomena in terms of their frequency.